1980
DOI: 10.1093/bja/52.6.609
|View full text |Cite
|
Sign up to set email alerts
|

Local Reactions to I.V. Diazepam in Three Different Formulations

Abstract: Local venous reactions during and after i.v injections of three different formulations of diazepam were studied in 200 patients undergoing gastroscopy. Of the patients receiving diazepam in propylene glycol (Stesolid) 78% experienced pain on injection and 48% subsequently developed clinical evidence of thrombophlebitis. The figures for Stesolid MR (diazepam in Cremophor EL) were 38% and 9% respectively. A significant decrease was achieved (pain on injection 1%; clinical thrombophlebitis 4%) when using Diazemul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1982
1982
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…Os exemplos clássicos de lesões vasculares decorrentes do tipo de drogas são: 1) glicose hipertônica (33) ; 2) diclofenaco (34) ; 3) difenil hidantoína (35) ; 4) diazepan (36) ; 5) praxilene (37) ; 6) epoprostenol (38) ; 7) anfotericina B (39) , além das lesões desencadeadas pela velocidade de infusão (40) . Para os cinco fatores de risco relacionados ao cateter intravascular e a sua permanência num mesmo sítio de inserção, obtivemos três fatores de risco com escores e" 0,80 (quadro 2); foi ainda observado o fator de risco Material de composição da agulha do cateter com escore 0,77 e cor do dispositivo com escore < 0,50.…”
Section: Método Método Método Método Métodounclassified
“…Os exemplos clássicos de lesões vasculares decorrentes do tipo de drogas são: 1) glicose hipertônica (33) ; 2) diclofenaco (34) ; 3) difenil hidantoína (35) ; 4) diazepan (36) ; 5) praxilene (37) ; 6) epoprostenol (38) ; 7) anfotericina B (39) , além das lesões desencadeadas pela velocidade de infusão (40) . Para os cinco fatores de risco relacionados ao cateter intravascular e a sua permanência num mesmo sítio de inserção, obtivemos três fatores de risco com escores e" 0,80 (quadro 2); foi ainda observado o fator de risco Material de composição da agulha do cateter com escore 0,77 e cor do dispositivo com escore < 0,50.…”
Section: Método Método Método Método Métodounclassified
“…Low concentration of propylene glycol in intravenous diclofenac injection produced a less adverse effect as compared to high propylene glycol concentration 7,9 . In one study investigators 14 found that diazepam in propylene glycol developed a higher incidence of thrombophlebitis as compared to diazepam dissolved in oil and emulsified in water without loss of therapeutic effect. Among three marketed compounds, Voveran is recommended for intravenous infusion while Jonac AQ and Dynapar AQ are recommended for intravenous bolus and infusion.…”
Section: Discussionmentioning
confidence: 99%
“…It is an oil-in-water emulsion in which the active ingredient, diazepam, has been dissolved in the oil phase ( 1 ). The frequency of localized venous side-effects using this preparation is lower than for water-based solutions of diazepam (2), which all contain several pharmacologically active organic solvents (3,4).…”
mentioning
confidence: 96%